2020
DOI: 10.3389/fimmu.2020.581241
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of IFN-γ Host Responses During Infection With Toxoplasma gondii

Abstract: Host defense against the human pathogen Toxoplasma gondii depends on secretion of interferon (IFN)-γ and subsequent activation of monocytic cells to combat intracellular parasites. Previous studies have shown that T. gondii evades IFN-γ-mediated immunity by secreting the effector TgIST into the host cell where it binds to STAT1, strengthens its DNA binding activity and recruits the Mi-2/NuRD complex to STAT1-responsive promoters. Here we investigated the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
(151 reference statements)
0
17
0
Order By: Relevance
“…Although the recruitment of Mi-2/NuRD was not required for the block mediated by the N terminal repeats, it may function in the regulation of other IFN-g induced genes. Consistent with this model, it has recently been suggested that recruitment of Mi-2/NuRD to IFN-g responsive genes is more import in secondary response genes where chromatin modulation may play a more important role 30 .…”
Section: Discussionmentioning
confidence: 61%
“…Although the recruitment of Mi-2/NuRD was not required for the block mediated by the N terminal repeats, it may function in the regulation of other IFN-g induced genes. Consistent with this model, it has recently been suggested that recruitment of Mi-2/NuRD to IFN-g responsive genes is more import in secondary response genes where chromatin modulation may play a more important role 30 .…”
Section: Discussionmentioning
confidence: 61%
“…Since the posttranslational modification (PTM) of histones plays a key role in epigenetic regulation and chromatin remodeling, similar PTM and gene expression changes in cyst-infected brain tissues would be another research direction to solve the mechanism of behavioral disorders induced by T. gondii. Nast et al (2020) also demonstrated that regulation of host histone marks during interferon gamma (IFN-g) immune response could be broadly inhibited by T. gondii. Until now, only a few of secreting effectors have been described as able to initiate host epigenetic signal: the rhoptry protein ROP16 and ROP18 and the dense granule protein GRA15, GRA16,GRA24, TEEGR, and TgIST.…”
Section: Advances Of Epigenetic Regulation In T Gondii-induced Behavi...mentioning
confidence: 99%
“… Nast et al. (2020) also demonstrated that regulation of host histone marks during interferon gamma (IFN-γ) immune response could be broadly inhibited by T. gondii .…”
Section: Advances Of Epigenetic Regulation In T Gondii ...mentioning
confidence: 99%
“…Multiple epigenetic enzymes have been identified to regulate the production and subsequent effect of IFNs in allogeneic T cells (102)(103)(104). A number of chemical compounds that selectively inhibit these enzymes are made available, and their effect on IFN signaling and therapeutic potentials are under active investigation (104)(105)(106). Since there are very limited reports studying the epigenetic regulation of type I IFNs in the GVHD context, our continual discussion will focus on the epigenetic effects on IFN-g.…”
Section: Epigenetic Programs and Pharmacological Modulations That Control Ifns In Allogeneic T Cells During Gvhdmentioning
confidence: 99%